Human capital, unemployment, FDI, labor productivity and gross domestic product - Indrajaya, Danang; Driyastutik, Windari (Jurnal Mantik, 2024)
The economic performance of a country can be evaluated by looking at Gross Domestic Product, which is considered one of the most significant measurement. The factors that drive economic growth are Human Capital, Unemployment, FDI, and Labor Productivity. China, Japan, South Korea, India and Australia have important roles not only in their strategic location but also rapidly developing into regional economic centers in the world. The purpose of this study was to analyze the effect of Human Capital, Unemployment, FDI, Labor Productivity on Gross Domestic Product in these countries of China, Japan, South Korea, India and Australia using cross section data for 10 years from 2010 to 2019. The results show that Human Capital and FDI have a positive and significant effect on Gross Domestic Product. While other variables have no significant effect on Gross Domestic Product. These findings show that the key factors influencing economic growth are investments in education, training, human resource development, and foreign direct investment